Studying the physical and chemical regularities of the interaction of calcium oxide with water - Шапорев, Валерий Павлович; Питак, Инна Вячеславовна; Васильев, Михаил Ильич; Питак, Олег Ярославович (Eastern-European Journal of Enterprise Technologies, 2015)
The paper presents an analysis of the experiment findings in the study of the processes of water hydration of СаОfree at different ratios of CaO/H2O and different activity of CaO. The analysis of the regularities in the processes of obtaining lump CaO and hydration of the samples proved that the reactivity of CaO is predetermined by the concentration of point defects in the lattice, and the ionoicity proportion in the Ca-O compound. The highest reactivity was achieved at 1473 K, the lowest – at 1773 K. The experimental data on the hydration of CaO of different activity at various ratios of CaO/H2O allowed confirming the fact that the mechanism of interaction between CaO and water has a series of sequential steps, such as: (1) the capillary water absorption by the sample, (2) chemisorption of water on the surface of CaO crystals, and (3) formation of end products of СаО(ОН)2solid or Са(ОН)2 slurry. The proposed equation is aimed at determining the velocity of the capillary water absorption depending on the reactivity of the CaO samples and properties of the liquid phase. It is found that the rate of the specific surface of the hydrated sample is commensurate with the rate of Са(ОН)2 formation.